A New Singular Impulsive Delay Differential Inequality and Its Application. (8th March 2009) - Ma, Zhixia; Wang, Xiaohu
Abstract : A new singular impulsive delay differential inequality is established. Using this inequality, the invariant and attracting sets for impulsive neutral neural networks with delays are obtained. Our results can extend and improve earlier publications.